Language Education Research Trend Across Pre-, During, and Post-COVID-19 and the Contribution of Indonesia - Riki Nasrullah; Parmin Parmin; Fahmy Lukman; Arditya Prayogi (Ranah: Jurnal Kajian Bahasa, 2025)
This study presents a bibliometric analysis of language education research from 2014 to 2024, emphasizing shifts before, during, and after the COVID-19 pandemic and highlighting Indonesia’s contribution within the global research landscape. Using Scopus-indexed data, 1,258 documents were analyzed based on publication trends, document types, source titles, co-authorship networks, and keyword co-occurrences. The analysis shows a significant increase in research on digital pedagogy, distance learning, and multilingual equity, particularly during and after the pandemic. While Indonesia's contribution remains proportionally modest, its research themes have increasingly aligned with global trends, especially in culturally responsive teaching and technology-enhanced learning. The study recommends future research directions focusing on critical language pedagogy, equity in multilingual education, and post-pandemic resilience in language teaching policies. These findings underscore the dynamic, adaptive trajectory of language education research over the past decade. Abstrak Penelitian ini menyajikan analisis bibliometrik penelitian pendidikan bahasa dari tahun 2014 hingga 2024, dengan menekankan pergeseran sebelum, selama, dan setelah pandemi COVID-19 serta menyoroti kontribusi Indonesia dalam lanskap penelitian global. Dengan menggunakan data yang terindeks Scopus, 1.258 dokumen dianalisis berdasarkan tren publikasi, jenis dokumen, judul sumber, jaringan kepenulisan bersama, dan kemunculan bersama kata kunci. Hasil analisis menunjukkan adanya peningkatan yang signifikan dalam penelitian tentang pedagogi digital, pembelajaran jarak jauh, dan kesetaraan multibahasa, terutama selama dan setelah pandemi. Meskipun kontribusi Indonesia secara proporsional masih kecil, tema-tema penelitiannya semakin selaras dengan tren global, terutama dalam hal pengajaran yang tanggap budaya dan pembelajaran yang didukung oleh teknologi. Studi ini merekomendasikan arah penelitian di masa depan yang berfokus pada pedagogi bahasa kritis, kesetaraan dalam pendidikan multibahasa, dan ketahanan pasca pandemi dalam kebijakan pengajaran bahasa. Temuan-temuan ini menggarisbawahi lintasan penelitian pendidikan bahasa yang dinamis dan adaptif selama satu dekade terakhir.